Curcumin and ustekinumab cotherapy alleviates induced psoriasis in rats through their antioxidant, anti-inflammatory, and antiproliferative effects. (2nd January 2022) - Mousa, Ayman M.; Alhumaydhi, Fahad A.; Abdellatif, Ahmed A. H.; Abdulmonem, Waleed Al; AlKhowailed, Mohammad S.; Alsagaby, Suliman A.; Al Rugaie, Osamah; Alnuqaydan, Abdullah M.; Aljohani, Abdullah S. M.; Aljasir, Mohammad; Alwashmi, Ameen S. S.; Soliman, Khaled E. A.; et al.
Abstract: Introduction: Psoriasis is a chronic multifactorial inflammatory disease that affects 3% of people worldwide. Ustekinumab is a selective anti-IL-12/23 biologic that alleviates psoriasis, and curcumin is a natural, effective dietary turmeric extract applied to treat numerous diseases through its antioxidant and anti-inflammatory effects. Objective: The current study evaluated the therapeutic effects of curcumin and ustekinumab cotherapy (CUC) on imiquimod (IQ)-induced psoriasis in a rat model. Materials and methods: Twenty rats were divided into four groups, G1 (control group), G2 (IQ-treated group), G3 (IQ + ustekinumab), and G4 (IQ + CUC). Clinical, histopathological (HP), immunohistochemical (IHC), antioxidant, and biochemical investigations evaluated the efficacy of these drugs for treating IQ induced-psoriasis. Results: Rats of G2 exhibited clinical signs of psoriatic skin lesions (erythema, scaling, and skin thickening) with epidermal changes (acanthosis and parakeratosis). Additionally, the biochemical analysis revealed significant ( p  < 0.05) reductions in the levels of antioxidant biomarkers (SOD, GPx, and CAT) with significant ( p  < 0.05) elevations in psoriasis-related cytokines (TNF-α, IL-17A, IL-12P40, and IL-23). In contrast, CUC alleviated the psoriatic changes in G4 better than ustekinumab monotherapy in G3. Conclusions: Ustekinumab inhibits the inflammatory cytokines IL-12P40 and IL-23, while curcumin has antioxidant effects (increasing SOD, GPx, and CAT levels) with anti-inflammatory effects (decreasing the proinflammatory cytokine TNF-α and IL-17). Therefore, CUC could be an excellent cost-effective regimen that can improve the treatment of psoriasis by the synergistic effects of CUC. Highlights: IQ-induces psoriasis by elevating TNF-α, IL-17A, IL-12, and IL-23 and decreasing GPx, SOD, and CAT Ustekinumab exhibits anti-inflammatory effects by inhibiting IL-12 and IL-23 Curcumin inhibits TNF-α and IL-17A, and increases GPx, SOD, and CAT levels CUC mitigates psoriasis by synergistic antioxidant and anti-inflammatory effects CUC inhibits TNF-α, IL-17A, IL-12, and IL-23 and increases GPx, SOD, and CAT levels